Host regulation of the legume-rhizobia symbiosis - Clark, LJ (2021)
Leguminous plants host nitrogen-fixing bacteria, known as rhizobia, in specialised root nodules, providing them with carbon in return for nitrogen. However, plants face an investment dilemma, as they usually house multiple strains of rhizobia that can vary in their fixation ability. This thesis characterises the host plant response to poorly fixing strains and compares this across nodule types.